The role of Libyan Universities, transfer and marketing the knowledge (Economic studies journal, 2024)
This study aims to identify the role of Libyan universities in technology transfer and marketing, in addition to the challenges they face. The descriptive analytical approach was adopted. Subsequently, a questionnaire was distributed on senior directly related to the technology transfer and marketing among twelve Libyan universities located  over the various geographical regions of the Libyan state. The study came up with many results, most important of which that the studied sample has a good level of awareness of technology transfer and marketing. While it suffered from difficulties related to the transfer of technology to society, scientific research, and cooperation with governmental and industrial institutions. Accordingly, the study provides a set of recommendations such as the urgent need to develop the educational system by moving towards experimental education, and incorporating pioneering thinking and technological and social innovation directed at solving society’s problems in all aspects. In addition, establishing  a technology transfer offices in Libyan universities, framing laws that guarantee intellectual property, administrative and financial independence, collecting self-revenue, establishing entrepreneurial companies within Libyan universities, and strengthening communication between Libyan universities, industry, investors, and businessmen locally and internationally.
Keywords: Knowledge transfer; technology transfer; technology commercialization; technological innovation; academic entrepreneurship; licensing; startups